Prognostic factors and overall survival among patients with ovarian cancer in the pre-PARP inhibitor era: the OCRWE-Finland study - Lahelma, Mari; Rauhamaa, Heini; Leskelä, Riikka-Leena; Isomeri, Outi; Idänpään-Heikkilä, Juhana; Käkelä, Sari; Roebuck, Nichola; Mascialino, Barbara; Hietanen, Sakari; Loukovaara, Mikko; Auranen, Annika (MJS Publishing, Medical Journals Sweden AB, 2025)
Background: Despite recent treatment advances in ovarian cancer (OC), more real-world evidence studies investigating patient outcomes are needed. OCRWE-Finland was an observational cohort study investigating OC outcomes in Finland during the pre-PARP inhibitor era.
Patients: Patients were diagnosed with OC between 2014 and 2019 in Finland. This analysis reports baseline characteristics of all patients, patients with high-grade serous OC (HGSOC), and overall survival (OS) for patients with HGSOC.
Results: Among 1,711 patients diagnosed with OC, 867 (51%) had HGSOC. The absence versus presence of visible residual disease post-debulking surgery was associated with improved OS for patients at stage III (n = 303; median: NR vs. 43 months; p = 0.005), but not stage IV (n = 118; median: 37 months vs. 40 months; p = 0.96). Bevacizumab treatment at any line at stages III/IV improved OS in the short-term only. Receiving versus not receiving bevacizumab at first-line for patients with visible residual disease post-debulking surgery was associated with improved OS at stage III (median: 48 months vs. 36 months; p = 0.003), but not stage IV (median: 42 months vs. 37 months; p = 0.26). Multivariate Cox regression analyses showed that stage IV at initial diagnosis and the presence of R2 classification post-debulking surgery resulted in poorer OS.
Interpretation: In the pre-PARP inhibitor era, the absence versus presence of visible residual disease post-debulking surgery was associated with improved OS in stage III, but not stage IV HGSOC. First-line bevacizumab seemed to be beneficial in patients with stage III HGSOC and visible residual disease.